Digital reconstruction of the Ceprano calvarium (Italy), and implications for its interpretation - Di Vincenzo, Fabio; Profico, Antonio; Bernardini, Federico; Cerroni, Vittorio; Dreossi, Diego; Schlager, Stefan; Zaio, Paola; Benazzi, Stefano; Biddittu, Italo; Rubini, Mauro; Tuniz, Claudio; Manzi, Giorgio (Scientific reports, 2017)
The Ceprano calvarium was discovered in fragments on March 1994 near the town of Ceprano in southern Latium (Italy), embedded in Middle Pleistocene layers. After reconstruction, its morphological features suggests that the specimen belongs to an archaic variant of H. heidelbergensis , representing a proxy for the last common ancestor of the diverging clades that respectively led to H. neanderthalensis and H. sapiens . Unfortunately, the calvarium was taphonomically damaged. The postero-lateral vault, in particular, appears deformed and this postmortem damage may have influenced previous interpretations. Specifically, there is a depression on the fragmented left parietal, while the right cranial wall is warped and angulated. This deformation affected the shape of the occipital squama, producing an inclination of the transverse occipital torus. In this paper, after X-ray microtomography (μCT) of both the calvarium and several additional fragments, we analyze consistency and pattern of the taphonomic deformation that affected the specimen, before the computer-assisted retrodeformation has been performed; this has also provided the opportunity to reappraise early attempts at restoration. As a result, we offer a revised interpretation for the Ceprano calvarium’s original shape, now free from the previous uncertainties, along with insight for its complex depositional and taphonomic history.